2007
DOI: 10.1902/jop.2007.060303
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Involvement of Oral Lichen Planus

Abstract: Considering the high frequency of gingival involvement in OLP, the diversity of clinical manifestations, and its potential relationship with general and oral health in patients, periodontists should be familiar with the most common clinical aspects of OLP in the gingiva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
(18 reference statements)
4
25
0
1
Order By: Relevance
“…3,4 Treatment options include potent topical corticosteroids, topical tacrolimus, intralesional corticosteroids, systemic corticosteroids, systemic retinoids, dapsone, mycophenolate mophetil, intravenous immunoglobulins, cyclosporin, and azathioprine. [1][2][3][4] However, these modalities are not always effective or associated with adverse effects when used for sustained periods of time. Our decision to use apremilast for EOLP was based on the mechanism of action of apremilast and the pathogenesis of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Treatment options include potent topical corticosteroids, topical tacrolimus, intralesional corticosteroids, systemic corticosteroids, systemic retinoids, dapsone, mycophenolate mophetil, intravenous immunoglobulins, cyclosporin, and azathioprine. [1][2][3][4] However, these modalities are not always effective or associated with adverse effects when used for sustained periods of time. Our decision to use apremilast for EOLP was based on the mechanism of action of apremilast and the pathogenesis of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…A review of previously published studies concluded that the risk of developing squamous cell carcinoma in patients with oral lichen planus was approximately 10 times higher than that in the unaffected general population. The study of the microcirculation in lingual lichen planus (LLP) would be important in the interception of the evolution of LLP (13,14). Capillaroscopy applied to lingual mucosa is a reliable method, useful for study and monitoring of oral lichen planus, if combined with the current conventional methods (15,16).…”
Section: Oral Capillaroscopy and Autoimmune Pathologiesmentioning
confidence: 99%
“…DG constitutes the gingival manifestation of several mucocutaneous disorders and systemic conditions. It has been reported in association with oral lichen planus (OLP), oral lichenoid lesions, mucous membrane pemphigoid, pemphigus vulgaris, erythema multiforme, graft‐versus‐host disease, lupus erythematosus, paraneoplastic pemphigus, epidermolysis bullosa acquisita, linear IgA disease, chronic ulcerative stomatitis, plasma cell gingivitis, dermatitis herpetiformis, foreign body gingivitis, and psoriasis 2‐15 …”
mentioning
confidence: 99%